Impressions from Sinop Regional Seminar on Public Libraries - Merve Ceren Tüzün; Ömer Çetin (Türk Kütüphaneciliği)
Impressions from Sinop Regional Seminar on Public Libraries hosted by Sinop Public Library and held in cooperation with Turkish Librarians’ Association, General Directorate of Libraries and Publications, Hacettepe University Department of Information and Document Management and Goethe Institute on May 20-22, 2011 are conveyed by Merve Ceren Tüzün ve Ömer Çetin, a sophomore student at the Hacettepe Üniversitesi Department of Information and Document Management.